Neuralgic amyotrophy presenting to an accident and emergency department. - Darby, M J (1997)
Two patients with neuralgic amyotrophy (Parsonage-Turner syndrome) are described. Problems arising from the shoulder girdle commonly present to accident and emergency (A&E) departments. Neuralgic amyotrophy is an infrequent neuromuscular disorder which predominantly affects the shoulder girdle. Characterised by severe pain followed by muscle weakness, atrophy, and variable sensory deficits, the diagnosis is based on history and physical findings and is confirmed by electromyography. The prognosis is excellent and treatment is supportive using analgesia and physiotherapy.